Developing Students’ Creativity through The Kurassaki Program at The State Elementary School of 1 Kutabaru - Sulaya, Maya; Jamaludin, Ujang; Dewi, Ratna Sari (Universitas Pendidikan Indonesia Kampus Serang, 2024)
Education today has entered the 21st century, which requires students to have 21st-century capabilities, one of which is creativity. Given how important the development of creativity is in education, efforts to develop student creativity continue to be made. One way to develop creativity can be done by utilizing the Kurassaki program. This research was conducted to determine the teacher's role in developing student creativity through the Kurassaki program and reveal the supporting and inhibiting factors in developing student creativity through the Kurassaki program at the State Elementary School of 1 Kutabaru. The method used in this research was qualitative, under the data and facts obtained through observation outlined in field notes, documentation, and interviews with several sources. The results of this study demonstrated that 1) the teacher's role in developing student creativity included the teacher as organizer, facilitator or mediator, class manager, motivator, informer, inspirator or demonstrator, supervisor, mentor, initiator, corrector, and evaluator. 2) In developing student creativity through the Kurassaki program, supporting factors comprised the completeness of facilities and infrastructure, teaching staff, and parents. Meanwhile, the inhibiting factors encompassed a lack of communication and socialization, a lack of creative teachers, a lack of student courage, and a lack of parental support. Therefore, it is necessary to socialize and involve parents in implementing the Kurassaki program.